Integrative genetics and multiomics analysis reveal mechanisms and therapeutic targets in vitiligo highlighting JAK STAT pathway regulation of CTSS - Zi-yue Dong; Ming-jie He; Yong-kai Yu; Fang Wang; Peng-yuan Zhao; De-long Ran; De-shuang Fu; Qing He; Run-ping Yang; Jiang-an Zhang (Scientific Reports)
Abstract Vitiligo is a complex autoimmune disease characterized by the loss of melanocytes, leading to skin depigmentation. Despite advances in understanding its genetic and molecular basis, the precise mechanisms driving vitiligo remain elusive. Integrating multiple layers of omics data can provide a comprehensive view of disease pathogenesis and identify potential therapeutic targets. The study aims to delineate the genetic and molecular mechanisms of vitiligo pathogenesis using an integrative multiomics strategy. We focus on exploring the regulatory influence of the JAK/STAT pathway on Cathepsin S, a potential therapeutic target in vitiligo. Our GWAS-meta analysis pinpointed five druggable genes: ERBB3, RHOH, CDK10, MC1R, and NDUFAF3, and underwent drug target exploration and molecular docking. SMR analysis linked CTSS, CTSH, STX8, KIR2DL3, and GRHPR to vitiligo through pQTL and eQTL associations. Microarray and single-cell RNA-seq data showed differential expression of CTSS and STAT1/3 in vitiligo patients’ blood and skin lesions. Our study offers novel perspectives on vitiligo’s genetic and molecular basis, highlighting the JAK/STAT pathway’s role in regulating CTSS for antigen processing in melanocytes. Further research is needed to confirm these results and assess the therapeutic potential of CTSS and related genes.